An overview of jail-based competency restoration. (19th October 2020) - Kirkorsky, Scott E.; Gable, Mary; Warburton, Katherine
Abstract : Forensic populations in the United States are increasing, driven largely by a rise in individuals determined to be Incompetent to Stand Trial (IST). Across most states, including California, the number of mentally ill inmates awaiting competency restoration has increased dramatically in recent years. Traditionally, competency restoration has taken place in state hospitals, but incompetent inmates often experience a significant wait for state hospital beds because of the rising demand for beds in such facilities. The resulting waitlists, which range from days to months, have led to states being held in contempt of court for violating limits placed on how long incompetent defendants can be held in jail. Therefore, alternatives to state hospitalization for IST patients have been developed, including jail-based competency (JBCT) restoration programs. JBCT programs provide restoration services in county jails, rather than in psychiatric hospitals. The following article will review the nature of JBCT programs and will emphasize the structure and evolution of such programs within California.